Gas adsorption material and method for manufacturing the same
Patent Information
- Application Number
- JP2025064304
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-22
AI Technical Summary
【0011】 本発明により、水に対する耐久性が高く、且つ体積又は質量あたりのガス吸着量が高い、MOFを含むガス吸着材料を提供することが可能となる。
Smart Images

Figure 2026170645000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a gas adsorption material and a method for producing the same.
BACKGROUND ART
[0002] A metal-organic framework (hereinafter also referred to as "MOF") is a crystalline porous material composed of a metal and an organic ligand. By the combination of the metal and the organic ligand used, properties such as the pore size and surface shape of the MOF can be designed at the molecular level. MOFs are expected to be applied to, for example, adsorption materials and storage materials for gases such as CO2, heterogeneous catalysts, and conductive materials.
[0003] For example, Non-Patent Document 1 describes a gas adsorption material in which the surface of a metal oxide is converted to an MOF.
[0004] Patent Document 1 describes a composite material comprising a porous body having pores therein and a porous coordination polymer compound, wherein the porous body has a network structure of Si-O bonds obtained by copolymerization of dialkoxysilane and trialkoxysilane, and the porous coordination polymer compound is supported in the pores of the porous body. This document describes that the composite material can be used as a gas adsorbent.
PRIOR ART DOCUMENTS
PATENT DOCUMENTS
[0005]
PATENT DOCUMENT 1
NON-PATENT DOCUMENTS
[0006]
NON-PATENT DOCUMENT 1
SUMMARY OF THE INVENTION
[0007] As described above, techniques using MOFs as gas adsorption materials are known. However, MOFs may have low durability against water. For this reason, when such a MOF is applied to a gas adsorption material, there has been a problem that the MOF is decomposed by water, degrading the performance of the gas adsorption material. Furthermore, when a MOF is applied to a gas adsorption material, there has been a problem that the gas adsorption amount per volume or mass is not sufficient.
[0008] Accordingly, an object of the present invention is to provide a gas adsorption material containing a MOF that has high durability against water and a high gas adsorption amount per volume or mass. Means for Solving the Problems
[0009] The present inventors conducted various studies on means for solving the above problems. The present inventors have found that, in a gas adsorption material containing a MOF including divalent metal ions and pyrazine ligands, by using acrylonitrile-butadiene-styrene (hereinafter also referred to as "ABS") resin, which has high durability against water and high mechanical strength, as a binder in a specific content, a pellet-shaped gas adsorption material that has high durability against water and a high gas adsorption amount per volume or mass can be obtained. The present inventors have also found that in the production of such a gas adsorption material, decomposition of the MOF can be substantially suppressed by using an organic solvent capable of dissolving the ABS resin as the solvent of the binder solution. The present inventors have completed the present invention based on the above findings.
[0010] That is, the present invention encompasses the following aspects and embodiments. (Embodiment 1) Formula (I): M a (L)2M b F n (I) [wherein M a is a divalent copper ion (Cu 2+) or a divalent nickel ion (Ni 2+ ), L is a pyrazine ligand, M b is a trivalent aluminum ion (Al 3+ ), a tetravalent silicon ion (Si 4+ ), or a tetravalent titanium ion (Ti 4+ ), n is 5 or 6.] A gas adsorption material in the shape of a molded body, comprising a metal-organic framework (MOF) represented by and an acrylonitrile-butadiene-styrene (ABS) resin, The gas adsorption material, wherein the content of the ABS resin is 2 mass% or more relative to the total mass of the MOF and the ABS resin. (Embodiment 2) The metal-organic framework according to Embodiment 1, wherein the content of the ABS resin is in the range of 2 to 16 mass% relative to the total mass of the MOF and the ABS resin. (Embodiment 3) M a is a divalent copper ion (Cu 2+ ), M b is a tetravalent titanium ion (Ti 4+ ), and n is 6, The metal-organic framework according to Embodiment 1 or 2. (Embodiment 4) A material preparation step of preparing a metal-organic framework (MOF) represented by Formula (I) and an acrylonitrile-butadiene-styrene (ABS) resin; A binder solution preparation step of mixing the ABS resin and an organic solvent to prepare a binder solution; A material mixture forming step of mixing the MOF and the binder solution; A molding step of molding the material mixture; A method for producing the gas adsorption material according to any one of Embodiments 1 to 3, comprising the steps of. (Embodiment 5) The method according to Embodiment 4, wherein the organic solvent used in the binder solution preparation step is acetone or N,N-dimethylformamide (DMF). [Effects of the Invention]
[0011] The present invention makes it possible to provide a gas adsorption material containing an MOF that has high water resistance and high gas adsorption capacity per unit volume or mass. [Brief explanation of the drawing]
[0012] [Figure 1] The crystal structure of one embodiment of the MOF included in the gas adsorption material according to one aspect of the present invention is shown. [Figure 2] The X-ray diffraction patterns of the pellet-shaped gas adsorption materials of Examples 1 to 4 and 8, and Comparative Examples 4 and 5 are shown. In the figure, the horizontal axis represents the 2θ(Cu Kα) value (°), and the vertical axis represents the intensity (au). [Modes for carrying out the invention]
[0013] Preferred embodiments of the present invention will be described in detail below.
[0014] <1: Gas adsorption material> One aspect of the present invention relates to a gas adsorption material comprising a metal-organic frame (MOF) and a binder.
[0015] In the gas adsorption material of this embodiment, the MOF is given by formula (I): M a (L)2M b F n (I) It is expressed as follows: In equation (I), M a This is a divalent copper ion (Cu 2+ ) or divalent nickel ions (Ni 2+ ) and Cu 2+ It is preferable that L is a pyrazine ligand. b This is trivalent aluminum ions (Al 3+ ), tetravalent silicon ions (Si 4+ ), or tetravalent titanium ions (Ti 4+ ) and Ti 4+ It is preferable that n is 5 or 6, and is preferably 6. By including the MOF represented by formula (I), the gas adsorption material of this embodiment can have a high gas adsorption capacity.
[0016] In equation (I), M b Al 3+ In this case, 5 fluoride ions (F - ((M)) has a bi-trigonal pyramidal structure with 5 coordinates, and is a divalent anion b F5) 2- ) forms M b Si 4+ or Ti 4+ In this case, 6 F - ((M)) is a divalent anion having an octahedral structure with 6 coordinates. b F6) 2- ) forms.
[0017] In the gas adsorption material of this embodiment, the MOF is preferably Cu(pyrazine)2TiF6, Ni(pyrazine)2AlF5, Cu(pyrazine)2AlF5, or Cu(pyrazine)2SiF6, and more preferably Cu(pyrazine)2TiF6. By including an MOF having the structure represented by the above formula, the gas adsorption material of this embodiment can have a particularly high gas adsorption capacity.
[0018] In the gas adsorption material of this embodiment, the binder is ABS resin. ABS resin is known to have high water resistance and high mechanical strength. Therefore, the gas adsorption material of this embodiment, which contains ABS resin as a binder, not only has high water resistance but can also have a high gas adsorption capacity per unit volume or mass.
[0019] In the gas adsorption material of this embodiment, the ABS resin content is preferably 2% by mass or more, and within the range of 2 to 16% by mass, relative to the total mass of the MOF and the ABS resin. If the ABS resin content is less than the lower limit, it may not be possible to mold the gas adsorption material into the shape of a molded body. Therefore, by including the ABS resin in the range exemplified above, the gas adsorption material of this embodiment can be molded into the shape of a molded body.
[0020] The gas adsorption material of this embodiment is not in the form of MOF supported on a substrate, but rather in the form of a molded body in which the MOF and binder themselves are molded. The specific shape of the molded body is not particularly limited, but examples include pellets, monoliths, pipes, or fibers. By being a molded body in the shape exemplified above, the gas adsorption material of this embodiment can have a high gas adsorption capacity per unit volume or mass.
[0021] Figure 1 shows the crystal structure of one embodiment of the MOF contained in the gas adsorption material of this embodiment. As shown in Figure 1, the MOF contained in the gas adsorption material of this embodiment is a divalent transition metal ion M a (Cu 2+ or Ni 2+ ) is bridged by pyrazine in the ab axis direction. And the cation M a2+ and anions (M b F5) 2- or (M b F6) 2- These elements form a crystalline structure through ionic bonding in the c-axis direction. Due to this crystalline structure containing ionic bonding, the MOF contained in the gas adsorption material of this embodiment has low water resistance. In contrast to such MOFs, a gas adsorption material molded using ABS resin, which has high water resistance and high mechanical strength, has been found to have high water resistance. Therefore, the gas adsorption material of this embodiment can exhibit high water resistance.
[0022] The composition and crystal structure of the MOF contained in the gas adsorption material of this embodiment can be determined, for example, by measuring the X-ray diffraction pattern of the gas adsorption material. Furthermore, the pyrazine ligands contained in the MOF contained in the gas adsorption material of this embodiment can be determined, for example, by dissolving the MOF in a solvent and then removing the pyrazine ligands contained in the solution. 1 It can be identified by analysis using 1H-NMR.
[0023] The amount of gas adsorbed by the gas adsorption material in this embodiment can be evaluated, for example, by measuring the gas (e.g., CO2) adsorption isotherm of the gas adsorption material and calculating the amount of gas adsorbed at a predetermined gas pressure.
[0024] <2: Method for manufacturing gas adsorption materials> Another aspect of the present invention relates to a method for producing a gas adsorption material according to an aspect of the present invention. The method of this aspect includes a material preparation step, a binder solution preparation step, a material mixture formation step, and a molding step. The method of this aspect may optionally include a method for synthesizing an MOF, which includes an MOF material preparation step, an MOF material solution preparation step, and an MOF formation reaction step. Each step of the method of this aspect will be described below.
[0025] [2-1: MOF material preparation process] The method of this embodiment may optionally include a MOF material preparation step. This step is L, M a , hydrofluoric acid (HF), and M b This includes preparing it.
[0026] In this process, pyrazine ligand L, divalent copper ions, or nickel ions M are prepared. a HF, and trivalent or tetravalent metal ions M b This can be prepared by purchasing the metal itself or an inorganic salt containing the metal ion. a Examples of inorganic salts containing this include copper(II) nitrate trihydrate (Cu(NO3)2·3H2O) and nickel(II) nitrate hexahydrate (Ni(NO3)2·6H2O). b Examples of inorganic salts containing this compound include aluminum nitrate notahydrate (Al(NO3)3·9H2O), ammonium hexafluorosilicate ((NH4)2SiF6), and ammonium hexafluorotiatanate ((NH4)2TiF6).
[0027] [2-2: MOF material solution preparation process] The method according to this embodiment may optionally include a step of preparing an MOF material solution. This step includes preparing a solution containing the MOF materials described above. This step can be carried out by dissolving each MOF material together or separately in a solvent such as water or ethylene glycol. In this step, the dissolution of the MOF materials may be carried out by mixing the MOF materials using a mixing means used in the art (e.g., an agate mortar).
[0028] [2-3: MOF production reaction process] The method of this embodiment may optionally include an MOF formation reaction step. This step includes mixing the MOF material solutions described above to react the MOF materials.
[0029] In the aqueous solution preparation step described above, in the embodiment in which each MOF material is dissolved separately in water to prepare aqueous solutions containing each MOF material, it is preferable that this step includes mixing and reacting each aqueous solution. In this embodiment, the reaction temperature is preferably room temperature, and more preferably in the range of 10 to 40°C. The reaction time is preferably in the range of 1 to 100 hours.
[0030] In the embodiment described above, where each MOF material is dissolved together in a solvent such as ethylene glycol to prepare a solution containing the MOF materials, it is preferable that this step includes placing the solution containing the MOF materials in a pressure vessel and reacting it at a high temperature (e.g., 100°C). In this embodiment, the reaction time is preferably in the range of 1 to 100 hours.
[0031] By carrying out a method for synthesizing MOFs, including a MOF material preparation step, an MOF material solution preparation step, and an MOF formation reaction step, under the above conditions, the reaction can be efficiently carried out to obtain MOFs.
[0032] [2-4: Material preparation process] This process includes preparing MOF and ABS resin.
[0033] The MOF prepared in this process may be purchased or prepared by the MOF synthesis method described above. The ABS resin prepared in this process may also be purchased or prepared.
[0034] [2-5: Binder Solution Preparation Process] This process includes mixing ABS resin with an organic solvent to prepare a binder solution.
[0035] The organic solvent used in this process is preferably acetone or N,N-dimethylformamide (DMF). The organic solvents exemplified above can be purchased or otherwise prepared. The ABS resin used as a binder is highly lipophilic and therefore poorly soluble in water, but soluble in organic solvents. For this reason, a binder solution containing ABS resin can be prepared by carrying out this process using the organic solvents exemplified above.
[0036] [2-6: Material mixture formation process] This process includes mixing the MOF with the binder solution.
[0037] In this process, the mixing of the MOF and the binder solution can be carried out using mixing means used in the art (e.g., an agate mortar).
[0038] [2-7: Molding process] This process includes molding the material mixture.
[0039] In this process, the molding of the material mixture can be carried out using molding means used in the relevant technical field (e.g., extrusion molding or injection molding).
[0040] Water-soluble binders such as cellulose-based binders (e.g., hydroxypropyl methylcellulose) and alcohol-based binders (e.g., polyvinyl alcohol) are known in the relevant technical field. However, it has been found that when a gas adsorbent material is produced using a binder solution (aqueous solution) prepared by dissolving a water-soluble binder in water, the MOF may decompose by applying force in the presence of water during the material mixture forming step and / or the molding step. Therefore, by using an ABS resin as the binder and an organic solvent capable of dissolving the ABS resin as the solvent of the binder solution, it is possible to produce a gas adsorbent material in the form of a molded body while substantially suppressing the decomposition of the MOF.
[0041] As described in detail above, the gas adsorbent material according to one aspect of the present invention not only has high durability against water but also can have a high gas adsorption amount per volume or mass, as compared with conventional MOFs or gas adsorbent materials containing MOFs. Therefore, the gas adsorbent material according to one aspect of the present invention can be applied to an adsorption system, separation system or storage system for gases such as CO₂. In addition, the production method according to one aspect of the present invention can obtain the gas adsorbent material according to one aspect of the present invention having the characteristics described above in a high yield while substantially suppressing the decomposition of MOF. Therefore, the production method according to one aspect of the present invention can efficiently provide materials applicable to the uses exemplified above. [Examples]
[0042] Hereinafter, the present invention will be described more specifically with reference to Examples. However, the technical scope of the present invention is not limited to these Examples.
[0043] <I: Production of gas adsorbent material> [I-1: Reagents] Aluminum nitrate nonahydrate (Al(NO₃)₃·9H₂O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 98.0+ wt% Nickel(II) nitrate hexahydrate (Ni(NO₃)₂·6H₂O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 98.0+ wt% Copper(II) nitrate trihydrate (Cu(NO3)2·3H2O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 99.0 to 104.0% by weight Ammonium hexafluorosilicate ((NH4)2SiF6) (manufactured by Kanto Chemical Co., Ltd.) > 98.0% by weight Ammonium hexafluorotianoate ((NH4)2TiF6) (manufactured by Tokyo Chemical Industry Co., Ltd.) > 97.0% by weight Pyrazine (manufactured by Tokyo Chemical Industry Co., Ltd.) > 98.0% by weight Hydrofluoric acid (55% by mass HF) (manufactured by Hayashi Pure Chemical Industries, Ltd.) 55% by weight Ethylene glycol (manufactured by Nacalai Tesque Co., Ltd.) 99.5% by weight Ethanol (manufactured by Kanto Chemical Co., Ltd.) 94.8 to 95.8% by weight Acrylonitrile butadiene styrene (ABS) resin (ABS) Hydroxypropyl methylcellulose (HPMC) Polyvinyl alcohol (PVA) N,N-dimethylformamide (DMF)
[0044] [I-2: Synthesis of Ni(pyrazine)2AlF5] Distilled water is added to the solutes Al(NO3)3·9H2O and pyrazine to produce 0.64 mol·L of Al(NO3)3·9H2O. -1 , pyrazine 5.12 mol·L -1 Aqueous solution 1 containing the following concentration was prepared. Distilled water was added to the solute, hydrofluoric acid (55% by mass HF), to make 1.2 mol·L of HF. -1 Aqueous solution 2 containing the following concentration was prepared. Distilled water was added to the solute Ni(NO3)2·6H2O to make 0.64 mol·L of Ni(NO3)2·6H2O. -1Aqueous solution 3 containing the specified concentration was prepared (MOF material solution preparation step). 3 mL of polytetrafluoroethylene (PTFE) solution was mixed with 1 mL of aqueous solution 1, 0.5 mL of aqueous solution 2, and 0.5 mL of aqueous solution 3, and left at room temperature for 72 hours (MOF formation reaction step). The precipitate was collected. The precipitate was washed with aqueous solution 2 and then further washed with ethanol. The washed precipitate was dried under reduced pressure at 60°C overnight to obtain the product Ni(pyrazine)2AlF5.
[0045] [I-3: Synthesis of Cu(pyrazine)2AlF5] In the above I-2, the product Cu(pyrazine)2AlF5 was obtained under the same conditions as above, except that the solute in aqueous solution 3 was changed to Cu(NO3)2·3H2O of the same concentration.
[0046] [I-4: Synthesis of Cu(pyrazine)2SiF6] In an agate mortar, 1.21 g (5 mmol) of the raw materials Cu(NO3)2·3H2O, 3.56 g (20 mmol) of (NH4)2SiF6, and 3.20 g (40 mmol) of pyrazine, along with 6 mL of the solvent ethylene glycol, were added. The mixture was stirred in the agate mortar for 30 minutes to obtain the MOF material solution mixture (MOF material solution preparation step). This mixture was transferred to a 25 mL PTFE container. The PTFE container was placed in a pressure-resistant stainless steel outer cylinder and heated at 100°C for 48 hours (MOF formation reaction step). 10 mL of ethanol was added to the contents and stirred. The contents were centrifuged at 16,000 rpm for 15 minutes, and the supernatant was removed. The centrifugation and supernatant removal steps were repeated a total of four times. The washed precipitate was dried under reduced pressure at 60°C overnight to obtain the product Cu(pyrazine)2SiF6.
[0047] [I-5: Synthesis of Cu(pyrazine)2TiF6] In the same conditions as above, except that the materials were changed to Cu(NO3)2·3H2O 1.21 g (5 mmol), (NH4)2TiF6 3.96 g (20 mmol), and pyrazine 3.20 g (40 mmol), the product Cu(pyrazine)2TiF6 was obtained.
[0048] [I-6: Example 1] A binder solution was prepared by mixing ABS resin, which is the binder, with acetone, which is the solvent (binder solution preparation step). Ni(pyrazine)2AlF5, which is the MOF, was added to an agate mortar, and then the binder solution was added so that the ABS resin content was 8% by mass relative to the total mass of the MOF and ABS resin. The mixture was mixed in the agate mortar for 10 minutes while adding acetone as needed (material mixture formation step). The mixture was molded into a Φ2 mm rod shape by passing it through a mesh mold with Φ2 mm holes. The rod-shaped mixture was dried overnight at 60°C under reduced pressure in a vacuum. After that, the rod-shaped mixture was cut into 5 mm lengths to obtain MOF / ABS gas adsorption material in the form of pellet-shaped molded bodies (molding step).
[0049] [I-7: Example 2] In Example 1 (I-6), a gas adsorption material was obtained under the same conditions as described above, except that the MOF was changed to Cu(pyrazine)2AlF5.
[0050] [I-8: Example 3] In Example I-6 (Example 1), a gas adsorption material was obtained under the same conditions as described above, except that the MOF was changed to Cu(pyrazine)2SiF6.
[0051] [I-9: Example 4] In Example I-6 (Example 1), a gas adsorption material was obtained under the same conditions as above, except that the MOF was changed to Cu(pyrazine)2TiF6.
[0052] [I-10: Example 5] In the same conditions as described above, except that the ABS resin content was changed to 2% by mass relative to the total mass of the MOF and ABS resin, a gas adsorption material was obtained.
[0053] [I-11: Example 6] In the same conditions as described above, except that the ABS resin content was changed to 4% by mass relative to the total mass of the MOF and ABS resin, a gas adsorption material was obtained.
[0054] [I-12: Example 7] In the same conditions as described above, except that the ABS resin content was changed to 16% by mass relative to the total mass of the MOF and ABS resin in I-9 (Example 4), a gas adsorption material was obtained.
[0055] [I-13: Example 8] In the same conditions as described above, except that the solvent used in the ABS resin solution preparation step was changed to N,N-dimethylformamide (DMF) and the material mixture formation step was modified to mix in an agate mortar for 10 minutes without adding a solvent, a gas adsorption material was obtained.
[0056] [I-14: Comparative example 1] In the same conditions as described above, except that the ABS resin content was changed to 1% by mass relative to the total mass of the MOF and ABS resin, a gas adsorption material was obtained.
[0057] [I-15: Comparative example 2] In the same conditions as above, except that the binder used in the binder solution preparation step was changed to HPMC and the solvent to water, and the material mixture formation step was modified to mix in an agate mortar for 10 minutes without adding a solvent, a gas adsorption material was obtained.
[0058] [I-16: Comparative example 3] In the same conditions as above, except that the binder used in the binder solution preparation step was changed to PVA and the solvent to water, and the material mixture formation step was modified to mix in an agate mortar for 10 minutes without adding a solvent, a gas adsorption material was obtained.
[0059] [I-17: Comparative example 4] In the aforementioned I-12 (Example 7), a gas adsorption material was obtained under the same conditions as described above, except that the binder used in the binder solution preparation step was changed to HPMC, the solvent was changed to water, and in the material mixture forming step, no solvent was added and the mixture was mixed in an agate mortar for 10 minutes.
[0060] [I-18: Comparative Example 5] In the aforementioned I-12 (Example 7), a gas adsorption material was obtained under the same conditions as described above, except that the binder used in the binder solution preparation step was changed to PVA, the solvent was changed to water, and in the material mixture forming step, no solvent was added and the mixture was mixed in an agate mortar for 10 minutes.
[0061] <II: Analysis of Gas Adsorption Material> [II-1: Shape of Gas Adsorption Material] The components and shapes of the gas adsorption materials of Examples 1 to 8 and Comparative Examples 1 to 5 are shown in Table 1.
[0062]
Table 1
[0063] As shown in Table 1, in the cases of Examples 1 to 8 and Comparative Examples 4 and 5, pelletization was possible. In contrast, in the cases of Comparative Examples 1 to 3, pelletization could not be achieved, and the materials remained in powder form. From this result, it is inferred that if the binder content in the gas adsorption material is 2 mass% or more relative to the total mass of the MOF and the binder, pelletization can be performed using any MOF and binder.
[0064] [II-2: Analysis of Crystal Structure of Metal-Organic Framework Contained in Gas Adsorption Material] X-ray diffraction measurements were performed on the pellet-shaped gas adsorption materials of Examples 1 to 4 and 8, and Comparative Examples 4 and 5, respectively. The measurement apparatus and measurement conditions are shown below. The X-ray diffraction patterns of the powder of each product are shown in Figure 2. In the figure, the horizontal axis represents 2θ(Cu K α ) value (°), and the vertical axis represents intensity (a.u.). Measurement device: RINT RAPID II (Rigaku Corporation) Measurement conditions: Voltage 50 V, current 100 mA, collimator diameter φ0.3 mm, sample angle ω5°
[0065] As shown in the X-ray diffraction patterns of Figure 2, in Examples 1 to 4 and 8, MOF(M a (L)2M b F n Peaks corresponding to the 001 diffraction line and the 100 diffraction line were observed in (I). From this result, it is presumed that in Examples 1 to 4 and 8, the crystalline structure of the MOF is maintained even after molding into pellet shape. In contrast, in Comparative Examples 4 and 5, peaks corresponding to the 001 diffraction line and the 100 diffraction line were not observed. From this result, it is presumed that the MOF decomposes in the gas adsorption materials of Comparative Examples 4 and 5.
[0066] In Comparative Examples 4 and 5, water was used as the solvent for the binder solution during their manufacture. From these results, it is inferred that the MOFs contained in the gas adsorption materials of Comparative Examples 4 and 5 can be decomposed by applying force in the presence of water during the material mixture formation process and / or molding process. On the other hand, in Examples 1 to 4 and 8, organic solvents such as acetone or DMF were used as the solvent for the binder solution during their manufacture. From these results, it is inferred that the MOFs contained in the gas adsorption materials of Examples 1 to 4 and 8 do not decompose or cannot be easily decomposed even when force is applied in the presence of an organic solvent during the material mixture formation process and / or molding process.
[0067] These results demonstrate that by using ABS resin as a binder and an organic solvent capable of dissolving ABS resin as the solvent for the binder solution, it is possible to produce pellet-shaped gas adsorption materials while substantially suppressing the decomposition of MOFs.
[0068] It should be noted that the present invention is not limited to the embodiments described above, and various modifications are included. For example, the embodiments described above are described in detail to make the present invention easier to understand, and are not necessarily limited to those having all the configurations described. In addition, it is possible to add, delete, and / or replace some of the configurations in each embodiment with other configurations.
Claims
1. Equation (I): M a (L) 2 M b F n (I) [In the formula, M a This is a divalent copper ion (Cu 2+ ) or divalent nickel ions (Ni 2+ ) and L is a pyrazine ligand, M b is a trivalent aluminum ion (Al 3+ ), a tetravalent silicon ion (Si 4+ ), or a tetravalent titanium ion (Ti 4+ ). n is either 5 or 6. A gas adsorption material in the form of a molded body, comprising a metal-organic structure (MOF) represented by and acrylonitrile butadiene styrene (ABS) resin, The gas adsorption material wherein the ABS resin content is 2% by mass or more relative to the total mass of the MOF and the ABS resin.
2. The metal-organic structure according to claim 1, wherein the ABS resin content is in the range of 2 to 16% by mass relative to the total mass of the MOF and the ABS resin.
3. M a However, divalent copper ions (Cu 2+ ) and M b However, tetravalent titanium ions (Ti 4+ The metal-organic structure according to claim 1, wherein n is 6.
4. A material preparation step involves preparing a metal-organic structure (MOF) represented by formula (I) and acrylonitrile-butadiene-styrene (ABS) resin; A binder solution preparation step involves mixing ABS resin with an organic solvent to prepare a binder solution; A material mixture formation step involves mixing the MOF and the binder solution; A molding process in which a mixture of materials is formed into a shape; A method for producing a gas adsorption material according to claim 1, including the method described in claim 1.
5. The method according to claim 4, wherein the organic solvent used in the binder solution preparation step is acetone or N,N-dimethylformamide (DMF).
Citation Information
Patent Citations
Composite material, gas adsorbent and method for producing composite material
WO2018062504A1